(untitled) (Journal of Economic Research & Business Administration, 2016)
This article describes the model of corporate governance: Anglo-American, Continental, Japanese, as well as family. The comparative characteristic of all models of corporate governance. Also, the article describes the main approaches developed in the world practice in corporate governance. The authors provide a clear example of the advantages and disadvantages of these models in the management of the corporation. It describes the need to borrow more effective instruments in Kazakhstan’s corporate governance practices, which are successfully used abroad since Kazakhstan practice of corporate governance defined history of the domestic companies as a result of mass privatization and does not fit into any of the classical models. In our opinion, it is appropriate to use the most effective tools of international practices in corporate governance.